SARS-CoV-2 Transmission among Students after the Full Reopening of Schools - Bayhan, Gülsüm İclal; Akça, Halise; Akça Çağlar, Ayla; Kurt, Funda; Akcan Yıldız, Leman; Şenel, Saliha; Karacan, Can Demir (Journal of Pediatric Infectious Diseases, 2022)
Objective Closing of schools within the scope of the pandemic measures and switching to online education have negatively affected the mental and physical health of children as well as their education. The effect of complete reopening of schools on the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is not fully known. In the 2021–2022 academic year, the Ministry of National Education of Türkiye has decided to continue face-to-face education at all levels and in all private and public schools, by following a series of measures. There are no studies on school transmission reported from Türkiye since then. This study aimed to assess the dynamics of coronavirus diseases 2019 (COVID-19) transmission in schools by evaluating the data of the school contact screening outpatient clinic of a tertiary children's hospital.Methods According to the Ministry of National Education guidelines in Türkiye, all students in a class with two polymerase chain reaction (PCR)–confirmed COVID-19 cases are sent to their homes and have a SARS-CoV-2 PCR test on the fifth day. While the students with negative test results return to school, students who test positive continue to stay at home until the 10th day. The current study retrospectively analyzed the screening results of primary, middle, and high school students who presented at the school contact screening polyclinic during the first semester of the 2021–2022 academic season.Results There were a total of 11,608 presentations to the school contact screening polyclinic, and 1,107 children tested positive with SARS-CoV-2 PCR (9.5%). The median weekly positivity rate was 9.7% in primary school, 9.4% in middle school, and 5.6% in high school. The weekly positivity rate increased from the 16th week at all school levels; the positivity rates ran in parallel before this time but significantly increased from the 16th week to the half-term break.Conclusion The curve of the positivity rates in schools was similar to Türkiye's pandemic curve. In this respect, the low SARS-CoV-2 transmission in schools correlated with the low number of cases in the community.
Keywords: school; student; online education; transmission; COVID-19